Apparatus for connection to private circuits run by certain public telecommunication operators. Specification for apparatus forconnection to digital circuits with interfaces according to CCITT G-series Recommendations. G.703 services at 2048 kbit/s and 8448 kbit/s Part 8-8.1, (31st October 1990) - British Standards Institution,
No abstract available